Simple Stories for a Complicated World: An Interview with Filmmaker Izidore Musallam - Ciecko, Anne (Asian Cinema, 2009)
Film and television director, writer, and producer Izadore Musallam’s work stretches across national boundaries and explores shifting identities.1 Born and raised in the Middle East and educated as a filmmaker in North America, he continues to reside in Canada while making English and Arabic-language films at home and abroad. Musallam’s debut feature Foreign Nights (1989) dealt with cultural and generational clashes within the Arab diaspora with the story of a Canadian teen dancer and her traditional Palestinian parents; his follow-up Nothing to Lose (1994) is a gangster spoof about a French Canadian boxer. Heaven Before I Die (1997) is a comedy about a young man from Palestine who moves to Toronto, receives advice from the ghost of Lebanese poet Khalil Gibran played by Omar Sharif, and gets a job as a Charlie Chaplin imitator. Forbidden Fruit (2002) is an updated Adam and Eve story of the seduction of a priest.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4yMC4yLjE2Nl8x